Aeromonas veronii caused disease and pathological changes in Asian swamp eel Monopterus albus. (11th July 2019) - Xia, Lihai; Han, Panpan; Cheng, Xiaoli; Li, Youshen; Zheng, Chuwen; Yuan, Hanwen; Zhang, Wenbing; Xu, Qiaoqing
Abstract: More and more diseases were occurred in the aquaculture of Asian swamp eel. Bacterial isolates were collected from the pathogenic organs of diseased Asian swamp eels. A dominant strain, Aeromonas veronii JL‐01, was isolated and identified from the liver and intestine tissue of diseased Asian swamp eels. The symptoms of fish infected artificially with A. veronii were the same as those observed under natural infection. The mortality rate was 40%–80% and infected Asian swamp eels died 2–3 days after infection. Drug sensitivity tests showed that the isolated bacterium was highly sensitive to seven kinds of antibiotics, including cephalosporins, aminoglycoside, quinolones, tetracyclines (except Tetracycline), pheniclos, nitrofurans and sulfonamides. The bacterium was resistant to penicillins (except Piperacillin), macrolides, polypeptides and lincomycin. The histological changes in Asian Swamp Eel induced by A. veronii infection mainly occurred in the liver, intestines and kidney. A. veronii showed strong pathogenicity towards the Asian swamp eel, causing tissue damage and death. Gentamycin, doxycycline and sulfamethoxazole could be used for preventing and treat this disease.